The Definitive Signs in Islamic Law: Ijtihad and its Application in Establishing, Classifying, and Implementing these Signs - Al-Habtar, Mohammad Mushabbib Mohammad (Journal of Islamic and Religious Studies, 2024)
The term “sign” in Islamic law has two terminological uses. The first, in a general sense, includes all sections of the positive ruling such as cause, condition, and prohibition. The second, in a specific sense, refers to the “pure sign,” which distinguishes it from other sections of legal rulings. Pure signs are things, attributes, and meanings designated by Sharia to indicate the existence of a known positive legal ruling. Verifying their existence aids in implementing related obligatory legal rulings, their conditions, and reasons. Examples include light, shadow, sunset, the crescent moon, signs of permission and sanctuary, signs of feelings, the redness and yellowing of fruit, and the growth of beard hair. The research highlights the characteristics of pure signs, the diversity of signs for a single ruling, and the distinction between signs and similar concepts. It presents evidence for the necessity of ijtihad (diligence) in explaining signs, acknowledges commendable efforts in clarifying certain signs, and envisions the future use of modern technology in regulating legal signs. The study is structured into an introduction, two main sections, and a conclusion, organized into demands and issues that align with its objectives.